2021
DOI: 10.1371/journal.pone.0253426
|View full text |Cite
|
Sign up to set email alerts
|

Cultural efficacy predicts body satisfaction for Māori

Abstract: This paper examines the relationship between body mass index (BMI), self-esteem and self-reported confidence and capability in expressing oneself culturally as Māori (cultural efficacy) for 5,470 Māori who participated in Te Rangahau o Te Tuakiri Māori me Ngā Waiaro ā-Pūtea | The Māori Identity and Financial Attitudes Study (MIFAS) in 2017. Adjusting for demographics, self-reported health, education and socio-economic status, we found that a higher BMI was associated with lower body satisfaction and self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Cultural Efficacy, as a proxy measure of Māori enculturation, has been found to predict resilience against psychological distress (Muriwai et al, 2015), positive body satisfaction (Houkamau et al, 2021), increased subjective well-being (Houkamau & Sibley, 2010), and increased self-esteem (Matika et al, 2017). These are important findings and illustrate the need to continue to explore the protective function of enculturation for Māori.…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Cultural Efficacy, as a proxy measure of Māori enculturation, has been found to predict resilience against psychological distress (Muriwai et al, 2015), positive body satisfaction (Houkamau et al, 2021), increased subjective well-being (Houkamau & Sibley, 2010), and increased self-esteem (Matika et al, 2017). These are important findings and illustrate the need to continue to explore the protective function of enculturation for Māori.…”
Section: Ethnic Identitymentioning
confidence: 99%
“…The body image construct is complex and in a recent systematic review, for adolescents from Western countries, individual factors (self‐perception of body image), relational factors (opinions of parents, family, friends and colleagues) and environmental factors (school environment and perceived expectations of body image across mass‐media) were all influential 29 . Among New Zealand Maori, those with higher levels of cultural efficacy appear to have higher levels of body satisfaction, even at higher BMIs, which could be a protective factor against DEB/ED 30 . Also, compared to westernised populations where there is a generalised desire for thinness, indigenous Australian adolescents (Aboriginal, Torres Strait Islander) are more likely to desire a larger, more muscular build than their Caucasian peers 31 .…”
Section: Take Home Messagesmentioning
confidence: 99%
“…29 Among New Zealand Maori, those with higher levels of cultural efficacy appear to have higher levels of body satisfaction, even at higher BMIs, which could be a protective factor against DEB/ED. 30 Also, compared to westernised populations where there is a generalised desire for thinness, indigenous Australian adolescents (Aboriginal, Torres Strait Islander) are more likely to desire a larger, more muscular build than their Caucasian peers. 31 Yet, although available evidence indicates that DEB/ED are as prevalent, if not more prevalent, in indigenous populations, no validated, culturally/ethnic specific screening tools for DEB/ED in these populations exist.…”
mentioning
confidence: 99%
“…Therefore, it is important to assess whether factors such as body regard are also important to NSSI in Māori youth. Research has shown that greater Māori cultural efficacy is correlated with higher body satisfaction (Houkamau et al, 2021). Therefore, if body regard was a salient factor to NSSI, then Māori identity may serve as a protective factor against holding a negative body regard which may in turn protect against engaging in NSSI when one is emotionally dysregulated.…”
Section: Sample Characteristicsmentioning
confidence: 99%